Tumor microenvironment and immune evasion in head and neck squamous cell carcinoma - Elmusrati, Areeg; Wang, Justin; Wang, Cun-Yu (International journal of oral science, 2021)
Head and neck squamous cell carcinoma (HNSCC), an aggressive malignancy, is characterized by high morbidity and low survival rates with limited therapeutic options outside of regional surgery, conventional cytotoxic chemotherapy, and irradiation. Increasing studies have supported the synergistic role of the tumor microenvironment (TME) in cancer advancement. The immune system, in particular, plays a key role in surveillance against the initiation, development, and progression of HNSCC. The understanding of how neoplastic cells evolve and evade the immune system whether through self-immunogenicity manipulation, or expression of immunosuppressive mediators, provides the foundation for the development of advanced therapies. Furthermore, the crosstalk between cancer cells and the host immune system have a detrimental effect on the TME promoting angiogenesis, proliferation, and metastasis. This review provides a recent insight into the role of the key inflammatory cells infiltrating the TME, with a focus on reviewing immunological principles related to HNSCC, as cancer immunosurveillance and immune escape, including a brief overview of current immunotherapeutic strategies and ongoing clinical trials.